2021
DOI: 10.3390/math9182265
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Use of a Wind Turbine as an Energy Recovery Device in Transport Systems

Abstract: A wind turbine can act as an energy recovery device (ERS) in a comparable way to brakes (regenerative braking). When the velocity of a vehicle changes, the amount of energy related to it also changes. When its velocity decreases, the energy tends to dissipate. Over time, this dissipated energy has been ignored. For example, during the braking process, the kinetic energy of the vehicle was converted into heat. In recent years, society’s greater awareness of climate change, pollution, and environmental issues ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…This percentage is referred to as the utilisation factor, and it equals the area of the wind turbine that can be utilised relative to the total frontal area of the vehicle multiplied by the Betz Limit of the wind turbine. [40][41][42] The area of three MWT is 0.145 m 2 and the frontal area of the EV is about 2.5 m 2 . Using 0.4 as the Betz limit of the MWT, the utilisation factor is 0.022, which can be rounded to 0.02 (20%).…”
Section: Methodsmentioning
confidence: 99%
“…This percentage is referred to as the utilisation factor, and it equals the area of the wind turbine that can be utilised relative to the total frontal area of the vehicle multiplied by the Betz Limit of the wind turbine. [40][41][42] The area of three MWT is 0.145 m 2 and the frontal area of the EV is about 2.5 m 2 . Using 0.4 as the Betz limit of the MWT, the utilisation factor is 0.022, which can be rounded to 0.02 (20%).…”
Section: Methodsmentioning
confidence: 99%
“…Wind energy's fexibility ofers an alternative to reduce fossil fuel dependency [22]. Researchers have explored innovative concepts, such as harnessing wind energy from unconventional sources, to generate sustainable electricity [23]. Studies have also demonstrated the feasibility of using horizontal-axis wind microturbines in transport systems, recovering energy while vehicles are in motion [23].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have explored innovative concepts, such as harnessing wind energy from unconventional sources, to generate sustainable electricity [23]. Studies have also demonstrated the feasibility of using horizontal-axis wind microturbines in transport systems, recovering energy while vehicles are in motion [23]. In addition, researchers have proposed an assessment method to determine wind energy potential based on wind speed, direction, and power data [24].…”
Section: Introductionmentioning
confidence: 99%